Model Pembelajaran Project Based Learning Berbasis Tri N untuk Meningkatkan Keterampilan Menulis Teks Prosedur - Nurinawati Nurinawati; Siti Rochmiyati (Inovasi Pendidikan dan Anak Usia Dini, 2025)
Based on the results of initial interviews and observations, it was found that several students still experienced difficulties in writing procedural texts effectively. These difficulties included a lack of understanding of the structure and characteristics of procedural texts, challenges in expressing ideas in written form, limited ability to compose coherent and communicative sentences, and the use of monotonous learning models that failed to stimulate student motivation. This study aims to describe the implementation of the Project Based Learning (PjBL) model based on the Tri N approach (Niteni, Niroke, and Nambahake) to improve the procedural text writing skills of fourth-grade students at Sidomukti Elementary School, Ambal Sub-district, Kebumen Regency, as well as to identify the improvement in writing skills after its application. The research employed a descriptive qualitative method with data collection techniques including observation, tests, and documentation. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The findings revealed that the application of the PjBL model integrated with Tri N values significantly improved students’ ability to write procedural texts. The learning process was carried out through six main stages of PjBL: formulating essential questions, planning projects, creating schedules, monitoring student activities, testing results, and evaluating learning experiences. The integration with Tri N principles encouraged students to understand, imitate, and develop their writing skills gradually. Thus, the PjBL model based on Tri N proved effective in helping students overcome writing difficulties while also fostering creativity, independence, and active participation in the learning process.